2012
DOI: 10.1093/molbev/mss218
|View full text |Cite
|
Sign up to set email alerts
|

Coevolution Reveals a Network of Human Proteins Originating with Multicellularity

Abstract: Protein interaction networks play central roles in biological systems, from simple metabolic pathways through complex programs permitting the development of organisms. Multicellularity could only have arisen from a careful orchestration of cellular and molecular roles and responsibilities, all properly controlled and regulated. Disease reflects a breakdown of this organismal homeostasis. To better understand the evolution of interactions whose dysfunction may be contributing factors to disease, we derived the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
30
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 23 publications
(34 citation statements)
references
References 54 publications
4
30
0
Order By: Relevance
“…Consistent with our findings, it was previously shown that the node degree in interaction networks was higher for more ancient taxonomic nodes (41) and ancient proteins had high connectivity and centrality in protein interactomes (42). Moreover, it was observed that protein interaction networks partitioned into two subnetworks: one corresponding to the most ancient interactions and one related to the recently emerged interactions in animal evolution that are involved in cell division and cell communication (41). A high level of horizontal gene transfer between species, a mechanism by which new interactions may emerge, is also characteristic for early stages of evolution (43).…”
Section: Tracing Back the Evolution Of Protein-binding Sites To The Osupporting
confidence: 93%
See 1 more Smart Citation
“…Consistent with our findings, it was previously shown that the node degree in interaction networks was higher for more ancient taxonomic nodes (41) and ancient proteins had high connectivity and centrality in protein interactomes (42). Moreover, it was observed that protein interaction networks partitioned into two subnetworks: one corresponding to the most ancient interactions and one related to the recently emerged interactions in animal evolution that are involved in cell division and cell communication (41). A high level of horizontal gene transfer between species, a mechanism by which new interactions may emerge, is also characteristic for early stages of evolution (43).…”
Section: Tracing Back the Evolution Of Protein-binding Sites To The Osupporting
confidence: 93%
“…In addition, Bacteria have many specific transcription regulators that are involved in the xenobiotics-resistance response, as in the case of the HTH_XRE superfamily. Consistent with our findings, it was previously shown that the node degree in interaction networks was higher for more ancient taxonomic nodes (41) and ancient proteins had high connectivity and centrality in protein interactomes (42). Moreover, it was observed that protein interaction networks partitioned into two subnetworks: one corresponding to the most ancient interactions and one related to the recently emerged interactions in animal evolution that are involved in cell division and cell communication (41).…”
Section: Tracing Back the Evolution Of Protein-binding Sites To The Osupporting
confidence: 91%
“…In addition, we performed an evolutionary rate ratio analysis, as described in a previous study. 44 Details of data and analyses were provided in our previous study. 36 …”
Section: Computing Selective Pressure and Evolutionary Ratesmentioning
confidence: 99%
“…Furthermore, we performed an evolutionary distance analysis by comparing human sequences with orthologous sequences from other animals, as described previously. 44 …”
Section: Inferring Protein Evolutionary Originsmentioning
confidence: 99%
“…The relative rates of evolution for the proteins and their domains were calculated as described earlier 26 . Ortholog groups were obtain using the OMA Browser 27 and alignments were obtained with MAFFT 28 .…”
Section: Methodsmentioning
confidence: 99%